The individual and combined effects of air pollution mixtures on the risk of cardiovascular diseases in patients with Cardiovascular-Kidney-Metabolic syndrome at stages 0–3 - Fengjiao Han; Haiyang Guo; Yang Zheng (PLoS ONE, 2026)
Background This study aims to employ a prospective cohort design to quantitatively assess the association between exposure levels of common ambient air pollutants and the risk of cardiovascular disease (CVD) in patients across stages 0–3 of Cardiovascular-kidney-metabolic (CKM) syndrome. By doing so, it addresses a critical knowledge gap in environmental exposure research within this specific clinical context. Methods We analyzed baseline differences between CVD cases/controls using descriptive statistics, parametric/nonparametric tests, and Pearson correlations for air pollutants (PM₁, PM2.5, PM₁₀, NO₂, O₃). Cox regression (Models 1–3, adjusting for sociodemographic/behavioral factors) and RCS assessed pollutant-CVD associations. WQS/qgcomp models evaluated mixture effects via weighted indices and directional weighting. Sensitivity analyses used BKMR, WQS-CVD exposure-response curves, and 2-year lag to address reverse causality. Results In single-pollutant analyses, per-interquartile range (IQR) increases in PM₁, PM₂.₅, PM₁₀, and NO₂ were associated with 30% (HR = 1.30, 95% CI 1.17–1.45), 35% (HR = 1.35, 95% CI 1.21–1.51), 52% (HR = 1.52, 95% CI 1.35–1.70), and 30% (HR = 1.30, 95% CI 1.17–1.45) elevations in CVD risk, respectively. No significant association was found for O₃. In mixture analyses, all three quantile g-computation (qgcomp) models linked combined pollutant exposure to significantly higher CVD risk (Model 1: HR = 1.10, 95% CI 1.04–1.17; Model 2: HR = 1.11, 95% CI 1.04–1.18; Model 3: HR = 1.12, 95% CI 1.05–1.19). PM₁₀ emerged as the dominant driver of the mixture effect. Conclusion Higher exposure levels to ambient air pollutants are associated with an increased risk of cardiovascular disease in patients with Stage 0–3 CKM syndrome.